Evaluating e-government implementation in public service delivery - KENENISSA KEBEDE, Desta (KDI School, 2017)
The purpose of this study is to assess e-government implementation in public service delivery and to examine stakeholders/customers trust on e-government service. This study applied Technology Acceptance Model (TAM) to investigate factors affect e-government implementation. The results indicate that factors ICT infrastructure, human capital, online service, risks and barriers are significantly affected ease of use and usefulness of e-government services. Specifically, I investigate two major issues in my research – (1) the intention to improve egovernment service by selected organizations (2) service provider perception on stakeholder/customer trust on e-government service provided. This study also find that the intention to improve e-government service is better in all selected organizations. Whereas perceived stakeholders/customer trust level in e-government service is similar in all selected organizations which is insignificant.
Thesis(Master) --KDI School:Master of Public Policy,2017